Identitas dan Kepentingan Indonesia Berpartisipasi dalam UN Peacekeeping Operations pada Era Presiden Susilo Bambang Yudhoyono - Rani Eka Syahputri; Shary Charlotte Pattipelohy (Journal of International Relations Diponegoro, 2018)
Conflict is an intrinsic aspect that can not be avoided in social conditions. UNPeacekeeping Operations (UN PKO) became a form of UN to help conflict nations becomepeaceful by building military, police and civil forces. Indonesia is one of the most activeand sustainable countries within the United Nations PKO since 1957. In the era of SusiloBambang Yudhoyono's administration, Indonesia's participation and commitment to UNPKO has received international attention for having achieved more than once. This studythen has a purpose to know the results of changes in Indonesia's commitment in the UnitedNations PKO in the era of SBY. This research uses constructivism paradigm. The methodused in this research is explanative type research. The result of the change in Indonesia'scommitment to PKO of the United Nations is because SBY interpreted Indonesia's identityas 'one million zero friend enemies' and as a member state of the UN. The identity thenspawned a set of interests that motivated Indonesia to increase participation in the PKO ofthe United Nations.